Kohleausstieg 2030 unter neuen Vorzeichen - Egerer, Jonas; Grimm, Veronika; Lang, Lukas; Pfefferer, Ulrike (Wirtschaftsdienst, 2022)
The Russian attack on Ukraine and the German energy industry’s dependence on Russian gas are currently leading to a very tight supply situation, which could worsen in the coming winter. In the medium term, too, the import price for natural gas is likely to be significantly above historical levels as Europe becomes independent of Russian gas. These developments call for a reassessment of German energy policy, including for the energy transition in the power sector.
CRIS-Team Scopus Importer:2022-09-30